Analisis Koordinasi Unit Ramp Handling Dengan Unit Pasasi Dalam Mencapai Ground Time Maskapai Citilink di Bandar Udara Sultan Thaha Jambi - Khairunnisa Maizara; Sri Sutarwati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Ramp handling is the activity that coordinates all operations occurring from the moment the aircraft blocks on until it blocks off, ensuring that departures are on schedule while considering flight safety factors. One of the coordination tasks performed by ramp handling personnel to achieve the established ground time for the aircraft is to coordinate with the passenger service unit to determine the number of passengers and the amount of baggage that will be departing, as well as during the boarding process for passengers onto the aircraft. Additionally, they coordinate regarding the completeness of flight documents and ensure that all procedures are carried out properly and in accordance with applicable regulations in a timely manner. The purpose of this research is to understand the coordination between the ramp unit and the passenger service unit in achieving ground time at Citilink Airlines, to identify the factors and obstacles that may affect ground time, and to determine the efforts made to achieve ground time at Citilink Airlines. The purpose of this research is to understand the coordination between the ramp unit and the passenger services unit in achieving ground time at Citilink Airlines, to identify the factors and obstacles that may affect ground time, and to determine the efforts made to achieve ground time at Citilink Airlines.This study analyzes the coordination between ramp handling staff and passenger services personnel to achieve ground time for Citilink Airlines at Sultan Thaha Airport using qualitative research methods. The data sources utilized include primary data obtained from interviews, observations, and documentation, as well as secondary data. The research findings indicate that the coordination between ramp handling staff and passenger services personnel is well-established in achieving ground time for Citilink Airlines. However, there are factors that influence ground time, such as late arrivals, passenger delays, environmental factors, Air Traffic Control (ATC) issues, and technical factors. Efforts made to achieve ground time include implementing quick handling, issuing TDAM (Technical Delay Aircraft Maintenance), and securing manpower support to ensure timely operations.